Mexican biogeographic provinces: Map and shapefiles - Morrone, Juan J.; Escalante, Tania; Rodríguez-Tapia, Gerardo (Zootaxa, 2017)
We provide a map of the 14 biogeographic provinces of Mexico based on the ecoregions recognized for the country, which combine climatic, geological and biotic criteria. These provinces belong to the Nearctic region (Californian, Baja Californian, Sonoran, Chihuahuan Desert and Tamaulipas provinces), Neotropical region (Pacific Lowlands, Balsas Basin, Veracruzan and Yucatán Peninsula provinces) and the Mexican transition zone (Sierra Madre Occidental, Sierra Madre Oriental, Transmexican Volcanic Belt, Sierra Madre del Sur and Chiapas Highlands provinces). In order to facilitate future biogeographic analyses, we provide a file of the biogeographical regionalisation of Mexico by converting the map into a polygon shapefile and a raster file with all provinces. We also separately provide each of the provinces in vector and raster format. All the maps are in geographical and Lambert Conformal Conic projections.